Culture of Independent Character in Post Pandemic Mathematics Learning Activities on Elementary School - Cahyaning Fitria Prihutami; Budi Murtiyasa; Yulia Maftuhah Hidayati; Yeny Prastiwi; Laili Etika Rahmawati (Universitas Pendidikan Ganesha, 2022)
Character education is part of the education process. The Covid pandemic requires students to study from home resulting in neglecting the cultivation of independent characters so that they experience obstacles during post-pandemic meetings. This study aims to analyse civilizing independent character in Mathematics learning activities at the post-pandemic meeting at elementary school. This research use desciptive qualitative approach. The subject of study are the principal, teachers and students. Data collection techniques through documentation, interviews and observations. Data analysis techniques through reduction, display, conclusion and verification. Validity test using triangulation of sources and techniques. The results of the study show that teacher activities cultivate independent characters in post-pandemic mathematics learning meetings through initial activities during apperception, core activities by 1) Using methods according to the material, 2) Getting students used to being involved in the learning process, 3) Familiarizing students independently in solving problems and closing by providing motivation foster independence.